2013
DOI: 10.1021/jp312406f
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Hydroxyls and Water on a CeO2(111) Thin Film Surface: The Role of Oxygen Vacancy

Abstract: The interaction of atomic hydrogen and H 2 O with stoichiometric and partially reduced CeO 2 (111) thin films deposited on a Cu(111) substrate was investigated by temperature programmed desorption and X-ray photoelectron spectroscopy. On stoichiometric CeO 2 (111) surface, the adsorption of atomic H(g) leads to the formation of surface hydroxyl (OH(a)) and H 2 O(a) as well as the reduction of Ce 4+ into Ce 3+ . On reduced CeO 2 (111) surfaces, the stability of OH(a) was enhanced by the presence of oxygen vacan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
142
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 70 publications
19
142
1
Order By: Relevance
“…This impurity peak, which reaches a maximum atomic fraction of 14% of the oxygen photoelectron spectra, does not change appreciably with bias over the course of the experiment. Finally, the photoelectron peak with the highest binding energy (B2.2 eV higher than the lattice oxygen peak) is assigned to adsorbed OH À groups, consistent with prior photoemission and temperature-programmed desorption investigations [34][35][36][37] . We note, however, the binding energy is considerably larger than that reported by Zhang et al 32 Moreover, we observed that the binding energy difference between the OH and the lattice O changed with bias ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
“…This impurity peak, which reaches a maximum atomic fraction of 14% of the oxygen photoelectron spectra, does not change appreciably with bias over the course of the experiment. Finally, the photoelectron peak with the highest binding energy (B2.2 eV higher than the lattice oxygen peak) is assigned to adsorbed OH À groups, consistent with prior photoemission and temperature-programmed desorption investigations [34][35][36][37] . We note, however, the binding energy is considerably larger than that reported by Zhang et al 32 Moreover, we observed that the binding energy difference between the OH and the lattice O changed with bias ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
“…Chen et al . proposed that when water dissociates on the oxygen vacancies of the oxides, it generates H 2 and leaves oxygen occupying these vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…It was verified (not shown) that the molecular desorption of H 2 O occurs from low to high temperatures, which is related to the recombination of hydroxyls species [35]. The H 2 spectra show that both oxides generate this gas at low temperature (413 K).…”
Section: Resultsmentioning
confidence: 96%
“…Chen et al [35] studied the dissociation of H 2 O on CeO 2 . They showed that the adsorption of H 2 O on this oxide (reduced) creates hydroxyls species, which then react desorbing H 2 O and generating O lattice and O vacancy .…”
Section: Resultsmentioning
confidence: 99%